#TITLE_ALTERNATIVE# - FITRIANI (NIM : 10211072), SARI
Surface Nuclear Magnetic Resonance (Surface-NMR) method is a geophysical technique that can be used to directly detect the presence of water content in the subsurface. This method utilize the spin properties of hydrogen nuclei in water molecules to detect the presence of groundwater. In this Final Project, evolution of magnetization vector assuming ideal resonance condition and resonance offset condition, and 1 dimension voltage response of Surface-NMR of several models of subsurface water content distribution using coincidence Tx/Rx circular loop , are modelled. The magnetization vectors components will be defected perfectly with tilt angle 90 Ã‚Â° with Mx=0 in the case of ideal resonance. However, in the case of frequency offset, there will be an imaginary component Mx that will make the transverse magnetization complex. Surface-NMR signal response indicates that the water content at shallow depths contribute greatly to the NMR signal. While the water content in the deep layers wil produce weak NMR signals when the water content is not large enough.